Infection Related Inferior Alveolar Nerve Paresthesia in the Lower Premolar Teeth - Rachele Censi; Virna Vavassori; Andrea Enrico Borgonovo; Dino Re (Case Reports in Dentistry)
Introduction. The aim of this paper was to describe two cases of IAN infection-induced paresthesia and to discuss the most appropriate treatment solutions. Methods. For two patients, periapical lesions that induced IAN paresthesia were revealed. In the first case, the tooth was previously endodontically treated, whereas in the second case the lesion was due to pulp necrosis. Results. For the first patient, a progressive healing was observed only after the tooth extraction. In the second patient, the paresthesia had resolved after endodontic treatment. Conclusions. The endodontic-related paresthesia is a rare complication that can be the result of a combination of etiopathogenic mechanisms such as mechanical pressure on the nerve fibers due to the expanding infectious process and the production of microbial toxins. Paresthesia resulting from periapical lesions usually subsides through elimination of infection by root canal treatment. However, if there are no signs of enhancement, the immediate extraction of the tooth is the treatment of choice in order to prevent irreversible paresthesia because it was demonstrated that there is a correlation between the duration of mechanical or chemical irritation and the risk of permanent paresthesia.